(w-1)(w=6)

Simple and best practice solution for (w-1)(w=6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (w-1)(w=6) equation:



(w-1)(w=6)
We move all terms to the left:
(w-1)(w-(6))=0
We multiply parentheses ..
(+w^2-6w-1w+6)=0
We get rid of parentheses
w^2-6w-1w+6=0
We add all the numbers together, and all the variables
w^2-7w+6=0
a = 1; b = -7; c = +6;
Δ = b2-4ac
Δ = -72-4·1·6
Δ = 25
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$w_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$w_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{25}=5$
$w_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-7)-5}{2*1}=\frac{2}{2} =1 $
$w_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-7)+5}{2*1}=\frac{12}{2} =6 $

See similar equations:

| 81x^-1+4=45x^-1/2 | | (8x-x^2)^3=256x^2 | | 7(x+6)=51 | | 7(x+6)=67 | | 44+(x+1)=90 | | x=0.1^-2 | | (3x+1)+(x-9)=180 | | 5t^2+20t=-135 | | 5t^2+2t=-135 | | -9x-9=-27 | | 9x-11=15x+7 | | 2x-14=-3x+3 | | 4x^2+10x+4=2x+1 | | 7(-1.6+d)=14 | | 8x-10(17)=-66 | | 9/10p+1/5=2 | | 2(x-4)=3+10 | | 4(2y-5)=7(y+2) | | 0.6(x+8)=30 | | 5e-19=3e | | 5+4(2x-3)=(5x+6)+5 | | 1.1x-3.2=-1 | | 3(x-5)+4=2(3x-1) | | 3y^2+109y-616=0 | | x(2x-1)=3x+6 | | 27x3=351 | | Y^2-31y=0 | | -1-4n-3=17+3n | | 24+2n=48 | | 30=5w+20 | | 25=15+10g | | 3^x-2^x-65=0 |

Equations solver categories